2021
DOI: 10.3389/fpsyg.2021.722771
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Mindfulness Program on Mental Health in Students at an Undergraduate Program for Teacher Education: A Randomized Controlled Trial in Real-Life

Abstract: Background: In this study, we aimed to investigate the effects of a mindfulness program including Mindfulness-Based Stress Reduction (MBSR) on the mental health of student teachers when offered at their educational institution in a real-life context.Methods: A parallel randomized controlled trial (RCT) was conducted among self-selected student teachers at a Danish undergraduate program for teacher education in the autumns of 2019 and 2020. Participation was not recommended in case of (1) clinical depression or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…ARSQ has not been validated in a Danish context. However, previous Danish research studies have shown effect of MBSR on ARSQ dimensions ( Juul et al, 2020 , 2021a ; Diachenko et al, 2021 ). In the present study, all subscales except from Self and Somatic Awareness had acceptable Cronbach’s α .…”
Section: Methodsmentioning
confidence: 79%
“…ARSQ has not been validated in a Danish context. However, previous Danish research studies have shown effect of MBSR on ARSQ dimensions ( Juul et al, 2020 , 2021a ; Diachenko et al, 2021 ). In the present study, all subscales except from Self and Somatic Awareness had acceptable Cronbach’s α .…”
Section: Methodsmentioning
confidence: 79%
“…Although so far there has been no research that has revealed the effect of MBSR therapy on anxiety in the population of adolescence scholars who works on undergraduate theses, there are several studies that have found that MBSR group therapy is effective in reducing anxiety levels in scholars majoring in nursing and teacher education (Juul et al, 2021;McVeigh et al, 2021). In a longitudinal study by Dundas, Thorsheim, Hjeltnes and Binder (2016), MBSR therapy was also found to be effective in overcoming scholar's anxiety about academic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…This therapeutic modality was also found to be effective in reducing anxiety levels in college students. (Juul et al, 2021;McVeigh et al, 2021). Then in a longitudinal study by Dundas, Thorsheim, Hjeltnes, and Binder (2016), MBSR therapy was also found to be effective in overcoming students' anxiety about academic evaluation in lectures.…”
Section: Introductionmentioning
confidence: 97%
“…In contrast, the RCT from which this economic evaluation draws data has a lower than average risk of bias, followed students for up to 12 months and reported on safety 13. A more recent study has also found benefits in favour of mindfulness-based interventions improving student mental health 45…”
Section: Discussionmentioning
confidence: 99%